ANALISIS KARAKTERISTIK CAMPURAN ASPAL BETON (AC-WC) DENGAN CARA UJI MARSHALL (STUDI KASUS PROYEK PENINGKATAN JALAN SOEKARNO-HATTA KABUPATEN LAMPUNG TIMUR) - Sriharyani, Leni (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2012)
The study was conducted to determine the suitability of implementation of the work surface pavement layer in Jalan Soekarno Hatta East Lampung regency and road conditions after age 1 year of the JMF and the ISO standard is used, the Marshall test on asphalt mixture concrete (AC-WC) which is a surface layer of pavement and pavement conditions on visual observation in the field.